2021
DOI: 10.1590/1518-8345.4805.3422
|View full text |Cite
|
Sign up to set email alerts
|

Child health vulnerabilities during the COVID-19 pandemic in Brazil and Portugal

Abstract: Objective: to analyze the vulnerabilities of children in the access to primary health care during the COVID-19 pandemic in Brazil and Portugal. Method: documentary study based on Brazilian and Portuguese governmental guidelines issued between March and August 2020 regarding access of children to primary health care. Thematic analysis was based on the precepts of health vulnerability. Results: 13 documents were issued in both countries addressing access to vaccination and childcare. Due to the SARS-CoV-2, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
1
12
0
13
Order By: Relevance
“…The physical distancing in Brazil ranged between the regions, and the average was 6 months, a time considerably long compared to other countries. In both Brazil and Portugal, it has been identified that children and young people have had restrictions on health promotion services during the pandemic [21].…”
Section: Introductionmentioning
confidence: 99%
“…The physical distancing in Brazil ranged between the regions, and the average was 6 months, a time considerably long compared to other countries. In both Brazil and Portugal, it has been identified that children and young people have had restrictions on health promotion services during the pandemic [21].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that society has values of equality and social justice, as well as health services to fight against health inequities, are clear indicators that these aspects must be analyzed in scientific studies in order to produce evidence for public policies and internal coherence of these policies and their implementation in various sectors 28 - 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the concept of health inequalities is essential for health care. Self-care is strongly related to fulfilling health needs, which are seen not as the absence of illnesses 30 , but within the intercultural logic and intersubjectivity of human existence and dignity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Neves and Guerrero (2020) 19 proposed a model to predict the evolution of the virus in Brazil, and Cotta and colleagues (2020) 20 evaluated the impact of public health measures during the COVID-19 pandemic. The impact of the virus on the eating habits and physical activity of health care professionals are also explored, 21 as well as symptoms of depression, 22 child health vulnerabilities, 23,24 and SARS-CoV-2 mutations in Brazil. 25 Although many studies have explored the COVID-19 outbreak in the Brazilian context, most work has focused on analyzing specific issues related to the spread of SARS-CoV-2, drugs, and symptoms.…”
Section: Brief Backgroundmentioning
confidence: 99%